SITUS TINCO SEBAGAI PUSAT AWAL BERDIRINYA KERAJAAN SOPPENG PRAISLAM - Duli, Akin (Universitas Hasanuddin, 2019)
Research on the variability of the findings of archaeological data on the Tinco site in Soppeng Regency is very important to know about the function and role of the cultural heritage in the past. The method used is the archaeological survey and analysis analogous to historical (lontaraq) data from people who are still living in the community. The variability of archeological data such as various types of megalithic culture, foreign ceramics, pottery, fortifications, and ancient tombs shows that the site has a very important role in the past. The results of this study indicate that the Tinco site is based on evidence of cultural and natural conditions – it is strongly to indicate that it was the center of the early establishment of the Soppeng Kingdom in the past.